Новые палеарктические виды наездников рода Metopius (Hymenoptera, Ichneumonidae) - Толканиц, В.И. (Вестник зоологии, 1993)
Melopius (Tylopius) cerltts sp. n. (d) differs from any other species of the sub-genus in having pointed lower facial shield margin reaching lower margin of the clype-us. M. (Ceratopius) basarukini sp. n. (9) distinct from similar M. (C.) carinatus To 1 k. by absence of median carina along the middle of clypeus, by peculiarities of head and abdominal tergites yellow pattern, by brilliant blue metallic flush of abdominal tergites.